The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/eva.13082
|View full text |Cite
|
Sign up to set email alerts
|

How does contemporary selection shape oak phenotypes?

Abstract: Most forests worldwide are renewed by natural processes, the exception being artificially planted woodlands, which account for 7% of the world's forests (FAO, 2015). The remaining primary and secondary forests are regenerated by means of seedlings resulting from open pollination between mature trees. Natural processes dominated by competition for light, water and nutrients, and environmental disturbances, exert a strong influence during the early stages of development of the renewed forest stand. Human activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 93 publications
3
28
0
Order By: Relevance
“…We recently reported that Q. petraea forest stands display substantial heritable differences in reproductive success (Alexandre et al 2020). The genetic variance of fitness in a forest located between two of the forests studied here, Bercé and Réno-Valdieu, was 0.468 (Alexandre et al 2020), which is at the upper end of the range of values reported in a recent review of the literature (89% of the reported values were below 0.20) (Hendry et al 2018). In addition, most linkage disequilibrium is present in oak populations for physical distance lower that 5000 bp (Nocchi et al 2021), which corresponds to 0.0052 cM taking into account the physical and genetic maps of oak (Bodenes et al 2016;Plomion et al 2018).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…We recently reported that Q. petraea forest stands display substantial heritable differences in reproductive success (Alexandre et al 2020). The genetic variance of fitness in a forest located between two of the forests studied here, Bercé and Réno-Valdieu, was 0.468 (Alexandre et al 2020), which is at the upper end of the range of values reported in a recent review of the literature (89% of the reported values were below 0.20) (Hendry et al 2018). In addition, most linkage disequilibrium is present in oak populations for physical distance lower that 5000 bp (Nocchi et al 2021), which corresponds to 0.0052 cM taking into account the physical and genetic maps of oak (Bodenes et al 2016;Plomion et al 2018).…”
Section: Discussionmentioning
confidence: 48%
“…Buffalo and Coop (Buffalo & Coop 2019) showed that, under directional selection (based on an exponential fitness function), the covariances of neutral allele frequency changes over time depend on the genetic variance of fitness (VA), recombination distance (R) and linkage disequilibrium, and found that the amount of covariances accumulated over a few generations was mainly determined by the compound factor VA/R. We recently reported that Q. petraea forest stands display substantial heritable differences in reproductive success (Alexandre et al 2020). The genetic variance of fitness in a forest located between two of the forests studied here, Bercé and Réno-Valdieu, was 0.468 (Alexandre et al 2020), which is at the upper end of the range of values reported in a recent review of the literature (89% of the reported values were below 0.20) (Hendry et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly unequal distribution of individual reproductive success (Figure 4) has been observed repeatedly and seems to be a characteristic phenomenon in populations of oaks and other forest tree species (Alexandre et al, 2020;Gerber et al, 2014;Lepais & Gerber, 2011;Moran & Clark, 2012;Truffaut et al, 2017). Gerzabek et al (2017) hypothesized that strongly skewed individual reproductive success could be typical during the initial establishment phase of a population and will level out when population size and age increase.…”
Section: Discussionmentioning
confidence: 91%
“…This effect is pronounced enough, that even partial overtopping strongly limits an individual's reproductive success while completely overtopped individuals seem to drop out of the reproducing community entirely. This conclusion is backed up by Moracho et al (2018) who found a connection between tree fertility and size as well as Alexandre et al (2020) who observed strong variation in individual reproductive success and a clear relationship between reproductive success and growth. If individual tree size and social status (as a proxy for size and light exposure) are driving factors in determining individual reproductive success, the distribution of these two parameters among the individuals of a population will determine how pronounced the skew in individual reproductive success in this population will be.…”
Section: Discussionmentioning
confidence: 91%